2018
DOI: 10.5194/os-14-813-2018
|View full text |Cite
|
Sign up to set email alerts
|

Transport of FNPP1-derived radiocaesium from subtropical mode water in the western North Pacific Ocean to the Sea of Japan

Abstract: Abstract. This study investigated the spatio-temporal variations in activity concentrations in the Sea of Japan (SOJ) of 137Cs and these transport process from the North Pacific Ocean to the SOJ through the East China Sea (ECS) during 2012–2016. The 137Cs activity concentrations in the SOJ have been increasing since 2012–2013 and reached a maximum in 2015–2016 of approximately 3.4 Bq m−3, more than twice the pre-Fukushima accident 137Cs activity concentration of ∼1.5 Bq m−3. The 134Cs ∕ 137Cs activity ratios r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…17b). The 137 Cs activity concentrations in the Eastern China Sea and Japan Sea increased following the processes elucidated in our previous studies (Inomata et al, 2018). The increase in 137 activity in the surface mixed layer (0-50 m) in the Eastern China Sea reached a maximum in 2014/2015 (Inomata et al, 2018).…”
Section: Transport Of 137 Cs From the Pacific Ocean To The Indian Oce...supporting
confidence: 59%
See 2 more Smart Citations
“…17b). The 137 Cs activity concentrations in the Eastern China Sea and Japan Sea increased following the processes elucidated in our previous studies (Inomata et al, 2018). The increase in 137 activity in the surface mixed layer (0-50 m) in the Eastern China Sea reached a maximum in 2014/2015 (Inomata et al, 2018).…”
Section: Transport Of 137 Cs From the Pacific Ocean To The Indian Oce...supporting
confidence: 59%
“…The seasonal variation in the surface mixed layer depth might reflect the 0.5-yr average 137 Cs values in the western North Pacific Ocean. In addition, note that the behaviour, such as the transport pattern, of F1NPS-137 Cs is almost the same as that of 137 Cs derived from large-scale weapons tests in the 1950s-1960s (Aoyama et al, 2013(Aoyama et al, , 2016a(Aoyama et al, ,b, 2019(Aoyama et al, , 2020Inomata et al, 2012Inomata et al, , 2018.…”
Section: Transport Of 137 Cs From the Pacific Ocean To The Indian Oce...mentioning
confidence: 65%
See 1 more Smart Citation
“…According to the previous research based on the physical parameters in seawater, during the winter, the STMW is capped by the seasonal thermocline and then transported by the southwestward Kuroshio recirculation until approximately 20°N to south and east of Taiwan [ 50 , 51 ]. It was also found that the FNPP1 radiocaesium-labelled STMW was transported from NPSJ to the East China Sea (ECS), following then the Sea of Japan (SOJ) via the Tsushima Kaikyo, and transported into the North Pacific Ocean via the Tsugaru Strait within several years [ 52 ]. The integrated amount of FNPP1- 137 Cs that returned to the North Pacific Ocean through the Tsugaru Strait until 2016 was estimated to be 0.09 ± 0.01 Bq [ 52 ], which corresponds to 2.1% of the estimated total amount of FNPP1- 137 Cs in the STMW [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the FNPP1 radiocaesium-labelled STMW was transported from NPSJ to the East China Sea (ECS), following then the Sea of Japan (SOJ) via the Tsushima Kaikyo, and transported into the North Pacific Ocean via the Tsugaru Strait within several years [ 52 ]. The integrated amount of FNPP1- 137 Cs that returned to the North Pacific Ocean through the Tsugaru Strait until 2016 was estimated to be 0.09 ± 0.01 Bq [ 52 ], which corresponds to 2.1% of the estimated total amount of FNPP1- 137 Cs in the STMW [ 23 ]. This indicates that a small amount of the FNPP1- 134 Cs went back to the surface layer in the North Pacific Ocean.…”
Section: Discussionmentioning
confidence: 99%